Isolation and cultivation of Malaysian microalgae for biopharmaceutical application / Nur Nabiha Razak - Razak, Nur Nabiha (2014)
Microalgae are highly potential natural source of bioactive molecules for biopharmaceutical application. In this regard, work has been conducted to developed methods for the isolation of Malaysian microalgae strain, potentially valuable in biopharmaceutical application. Different microalgae strain may require different isolation strategies to adapt in in vitro culture. Four sampling regimes involving culturing of concentrated and non-concentrated water samples on TAP agar and TAP broth were carried out. Culturing onto TAP broth prior culturing onto TAP agar (Regime 3 and 4) were extremely essential for the recovery for microalgae strains from Temoh and Puncak Alam with a total recovery of 12 strains. Meanwhile, direct culturing of water samples onto TAP agar (Regime 1 and 2), resulted in the recovery of no microalgae from Temoh and six microalgae strains from Puncak Alam. Hence, to isolate microalgae from environment, specifically freshwater sources, culturing of collected water samples in both TAP broth and TAP agar simultaneously was proven to be necessary and important to isolate microalgae culture in vitro. Employment of all regimes will ensure maximum chance of microalgae recovery from freshwater sources. In obtaining axenic microalgae culture, the use of antibiotics was proven to be necessary. The regime that results in best recovery of axenic microalgae culture is by culturing non-axenic microalgae culture onto TAP-Amp (0.75 mg/mL). Microscopic examination of the isolated microalgae shows cell of different shapes including sphere, oval with tapered end and lanceolate shape. The diameter of microalgae range between 25 - 200 µm. Preliminary work on bioactive compound studies has indicated that there was no UV active bioactive compound detected in HPLC profile. However, the study of bioactive molecule should be continued as bioactive molecules produced by microalgae could potentially be utilized for biopharmaceutical application.